A simultaneous surgery of a giant abdominal aortic aneurysm and sigma carcinoma – a case report and a review of the literature - Wroński, Konrad; Okraszewski, Jerzy; Westfal, Tomasz; Bocian, Roman; Pakuła, Dariusz (Contemporary Oncology/Współczesna Onkologia, 2009)
The treatment of a patient with a simultaneous surgery of a giant abdominal artery aneurysm and sigma carcinoma still evokes a great deal of controversy at the same time posing a huge challenge for surgeons. Because of a small number of patients suffering from abdominal artery aneurysm and sigma carcinoma it is not quite clear whether to perform a simultaneous surgery consisting in an excision of the abdominal aortic aneurysm and sigma carcinoma, or perform two independent operations. Performing a simultaneous operation is connected with a risk of an aortic graft infection. In this article we present a case of a patient who underwent surgical treatment due to a giant abdominal artery aneurysm and sigma carcinoma. No complications in the postoperative period were observed, and the patient left hospital 8 days after the operations.